Crystalline structure of annealed polylactic acid and its relation to processing (eXPRESS Polymer Letters)
This paper focuses on the crystalline structure of injection moulding grade poly(lactic acid) (PLA) and the effect of crystalline structure on the processing. The research is induced by the significant differences in crystallinity of the pure PLA resin, and the injection moulded product, and thus the reprocessing of PLA products. 2 mm thick PLA sheets were injection moulded and re-crystallized in a conventional oven at 60–140°C, for 10–60 minutes to achieve various crystalline contents. The properties of these sheets were investigated by dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC), and wide angle X-ray diffraction (WAXD). In a processing plant the rejected parts are recycled and reused as raw material for further cycles, accordingly the various crystalline content PLA products were reprocessed as a resin, to investigate the processing itself. When PLA products are reprocessed, due to the adherent feature of amorphous PLA processing difficulties may occur. This adherent effect of the amorphous PLA was investigated and characterized.